Multifunctional electrochromic devices for energy applications - Kandpal, Suchita (2023)
A lot of development in terms of science and technology has taken place to address the increasing energy needs. This demand is expected to increase, especially due to environmental concerns associated with fossil fuels which have led to aggressive research toward energy storage materials and devices. Looking at this emerging trend, devices and materials that can convert, store, and save energy are the need of the hour. Electrochromic devices that assimilate these energy functionalities, along with bias-induced color modulation, are very promising as they not only help in energy conversion and storage but also help in energy saving when used as smart e-curtains for application in buildings and vehicles. The current Focus Review describes the promise of multifunctional electrochromic devices which can convert/generate and store energy through operations similar to batteries and supercapacitors. It also explains how electrochromism can prove to be a breakthrough in energy-related areas along with key challenges.